Cardiac Tamponade Following Port-a-Cath Insertion: A Case Report - Ranjitha Viswanathan; Venkatesh Selvaraj; Madhuri Galidevara Phani; Priadharsan Pavazhakannan; Sai Sanjana Manohar (Bali Journal of Anesthesiology)
Implantable port devices such as the port-a-cath device, inserted in infants, and the associated complications are under-reported, likely because of the limited indications for port placement. This case report describes the incidence of cardiac tamponade during insertion of a port-a-cath device in a 10-month-old infant with protein C and S deficiency. Chemo port insertion was planned in view of requirement of multiple fresh frozen plasma (FFP) transfusions. After induction of endotracheal general anesthesia, under ultrasound guidance, soon after insertion of the catheter over the guidewire, the child underwent hemodynamic instability, resulting in hypotension and bradycardia. On persistence of signs, immediate transthoracic echocardiography was carried out, which showed pericardial effusion. Needle pericardiocentesis was performed immediately under ultrasound guidance, and 20 mL of blood was aspirated. A pericardial pig tail catheter was left in situ. The 5 French port-a-cath is the smallest size available commercially, which we have used in this patient. The outer diameter of the 5 French port-a-cath is around 2.5 mm, which is equal to the average diameter of the internal jugular vein in infants, resulting in a catheter-to-vein diameter ratio of almost 1. The smaller size of the infant and the mismatch in the available sizes of this device contribute significantly to the technical difficulty of inserting this device in infants, leading to rare complication of pericardial tamponade. Ultrasound guidance should be used to locate the vein and confirm the position of the tip of the guidewire and the catheter during the process of insertion, which could have avoided this critical complication.